APLIKASI ELEKTROKOAGULASI UNTUK PENGOLAHAN LIMBAH BATIK - Fadli, Rizal Kharisma; Riswanto, Setya; aji, dewa; Widiasih, Wiwin (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2019)
Liquid waste and the problem will arise where the human activity, household liquid waste volume discarded can reach 60% more. Industrial liquid waste is about 30 - 40%, but is always considered a contributorthe biggest environmental polluters. Until now not many industries that do waste water treatmentto reduce the load of the pollutant produced before it is discharged into the water body. The main reason is the costoperational high enough. Preliminary processing such as aeration in a reservoir pond, the addition of a few chemicals to precipitate pollutants and pollutants, especially heavy metals which give rise to colors and harmful ought to be done by every industry. But because of the continuity of production and the duration of initial waste treatment that caused the entrepreneurs are reluctant to operate the initial processing earlier. Electrocoagulation is not a new technology, but in Indonesia has not been popular in its application. This process simple and easy to apply with good ability in clumping various impurities and pollutants, both organic and inorganic materials. In this study will be used galvalum plate. Research with a capacity of 25 Liters of treated waste, the specification of current suppliers 5 Ampere and 24 Volt. Variations of time 30, 60, 90 and 120 minutes. Keywords: pengolahan limbah cair, limbah batik, elektrokoagulasi, plat elektroda, rumah batik.